Management of breast cancer brain metastases: Focus on human epidermal growth factor receptor 2-positive breast cancer - Peng Yuan (KeAi Communications Co., Ltd., 2017)
After the introduction of trastuzumab, a monoclonal antibody that binds to human epidermal growth factor receptor 2 (HER2), the overall survival (OS) among patients with HER2-positive breast cancer has been substantially improved. However, among these patients, the incidence of brain metastases (BM) has been increasing and an increased proportion of them have died of intracranial progression, which makes HER2-positive breast cancer brain metastases (BCBM) a critical issue of concern. For local control of limited BM, stereotactic radiosurgery (SRS) and surgical resection are available modalities with different clinical indications. Postoperative or preoperative radiation is usually delivered in conjunction with surgical resection to boost local control. Adjuvant whole-brain radiotherapy (WBRT) should be deferred for limited BM because of its impairment of neurocognitive function while having no benefit for OS. Although WBRT is still the standard treatment for local control of diffuse BM, SRS is a promising treatment for diffuse BM as the technique continues to improve. Although large molecules have difficulty crossing the blood brain barrier, trastuzumab-containing regimens are critical for treating HER2-positive BCBM patients because they significantly prolong OS. Tyrosine kinase inhibitors are more capable of crossing into the brain and they have been shown to be beneficial for treating BM in HER2-positive patients, especially lapatinib combined with capecitabine. The antiangiogenic agent, bevacizumab, can be applied in the HER2-positive BCBM scenario as well. In this review, we also discuss several strategies for delivering drugs into the central nervous system and several microRNAs that have the potential to become biomarkers of BCBM. Keywords: Breast cancer brain metastases, Human epidermal growth factor receptor 2-positive breast cancer, Local control, Targeted therapy, MicroRNA